Genetic polymorphism analysis of the drug-metabolizing enzyme CYP1A2 in a Uyghur Chinese population: a pilot study. (2nd June 2016) - Geng, Tingting; Zhang, Xi yang; Wang, Li; Wang, Huijuan; Shi, Xugang; Kang, Longli; Hou, Peng; Jin, Tianbo
Abstract: 1. CYP1A2 is a highly polymorphic gene and CYP1A2 enzyme results in broad inter-individual variability in response to certain pharmacotherapies, while little is known about the genetic variation of CYP1A2 in Uyghur Chinese population. The aim of the present study was to screen Uyghur volunteers for CYP1A2 genetic polymorphisms. 2. We used DNA sequencing to investigate promoter, exons, introns, and 3' UTR of the CYP1A2 gene in 96 unrelated healthy Uyghur individuals. We also used SIFT (Sorting Intolerant From Tolerant) and PolyPhen-2 (Polymorphism Phenotyping v2) to predict the protein function of the novel non-synonymous mutation in CYP1A2 coding regions. 3. We identified 20 different CYP1A2 polymorphisms in the Uyghur Chinese population, including two novel variants (119A > G and 2410G > A). Variant 119A > G was predicted to be probably damaging on protein function by PolyPhen-2, by contrast, 2410G > A was identified as benign. The allele frequencies of CYP1A2*1A, *1B, *1F, *1G, *1J, *1M, *4, and *9 were 23.4%, 53.1%, 3.7%, 2.6%, 2.6%, 13.5%, 0.5%, and 0.5%, respectively. The frequency of *1F, a putative high inducibility allele, was higher in our sample population compared with that in the Caucasian population ( p < 0.05). The most common genotype combinations were *1A/*1B (46.9%) and *1B/*1M (27.1%). 4. Our results provide basic information on CYP1A2 polymorphisms in Uyghur individuals and suggest that the enzymatic activities of CYP1A2 may differ among the diverse ethnic populations of the world.